Faktor-Faktor Yang Berpengaruh Terhadap Cash Holdings - Sheila Marcel, Liana Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to examine the effect of firm size, leverage, net working capital and capital Expenditure on cash holdings. This study uses secondary data which was tested using eviews program 11.0. Samples that have been selected by purposive sampling method and selected as many as 73 manufacture companies as a sample from 185 companies that go public listed on the IDX for the period 2016 - 2018. The results of the research indicate that only firm size has a negative effect, while the other variables (leverage, net working capital and capital expenditure) have no significant effect on cash holdings.